The Effects of Media Coverage on the Dynamics of Disease in Prey-Predator Model - Walaa Madhat Alwan; Huda Abdul Satar (Iraqi Journal of Science, 2021)
In this paper, an eco-epidemiological model with media coverage effects is established and studied. An -type of disease in predator is considered. All the properties of the solution of the proposed model are discussed. An application to the stability theory was carried out to investigate the local as well as global stability of the system. The persistence conditions of the model are determined. The occurrence of local bifurcation in the model is studied. Further investigation of the global dynamics of the model is achieved through using a numerical simulation.